Estudo comparativo dos efeitos hemodinâmicos e ventilatórios da ventilação controlada a volume ou a pressão, em cães submetidos ao pneumoperitônio - Carraretto, Antonio Roberto [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; De Almeida, Armando Vieira [UNESP]; Ganem, Eliana Marisa [UNESP] (Elsevier, 2005)
BACKGROUND AND OBJECTIVES: Pressure controlled ventilation (PCV) is available in anesthesia machines, but there are no studies on its use during CO 2 pneumoperitoneum (CPP). This study aimed at evaluating pressure-controlled ventilation and hemodynamic and ventilatory changes during CPP, as compared to conventional volume controlled ventilation (VCV). METHODS: This study involved 16 dogs anesthetized with thiopental, fentanyl and pancuronium, which were randomly assigned to two groups: VC - volume controlled ventilation (n=8) and PC - pressure controlled ventilation (n=8). Hemodynamic and ventilatory parameters were monitored and recorded in 4 moments: M1 (before CPP), M2 (30 minutes after CPP = 10 mmHg), M3 (30 minutes after CPP=15 mmHg) and M4 (30 minutes after deflation). RESULTS: With CPP, there has been significant increase in tidal volume in PC group; there has been increase in airway pressures (peak and plateau), decrease in compliance with increase in CPP pressure, increase in heart rate, maintenance of mean blood pressure with higher values in the VC group in all stages; there was also increase in right atrium pressure with significant decrease after deflation, decrease in arterial pH with minor variations in PC group, greater arterial pCO 2 stability in PC group, and no significant changes in arterial pO 2. CONCLUSIONS: There were some differences in hemodynamic and ventilatory data between both ventilation control modes (VC and PC). It is possible to use pressure controlled ventilation during CPP, but the anesthesiologist must monitor and take a close look at alveolar ventilation, adjusting inspiratory pressure to ensure proper CO 2 elimination and oxygenation. © Sociedade Brasileira de Anestesiologia, 2005.
Hemodynamic and ventilatory effects of volume or pressure controlled ventilation in dogs submitted to pneumoperitoneum. Comparative Study
Keywords: ANIMAL, Dog; SURGERY, Abdominal: videolaparoscopic; VENTILATION: mechanically controlled; fentanyl; pancuronium; thiopental; airway pressure; arterial carbon dioxide tension; arterial oxygen tension; arterial pH; artificial ventilation; comparative study; controlled study; dog; heart rate; heart right atrium pressure; hemodynamic monitoring; lung compliance; lung ventilation; mean arterial pressure; nonhuman; pneumoperitoneum; randomization